Stella Manhattan de Silviano Santiago e Onde andará Dulce Veiga? De Caio Fernando Abreu: dois romances homotextuais brasileiros - Nascimento, Cyro Roberto de Melo (2019)
In this thesis we analyze how Brazilian homoerotic writing, which we will call homotextuality, was reconfigured in the 1960s and 1970s. During those decades, the emergence of new subjects of rights, influenced by the country's rapid urban development and its changing cultural values, allowed a writing about homosexuality from a new prism, in which the subjects themselves can speak openly about their desire. To guide our analysis, we chose the novels Stella Manhattan (1985) by Silviano Santiago and Onde andará Dulce Veiga? (1990) by Caio Fernando Abreu, two authors of great repercussion both for critics and public, whose works, even written later, situate their narratives at the 1960s and 1970s. We use Michel Foucault (1988) and Judith Butler´s (2000, 2013) concepts about sexuality as a historically demarcated and discursively instituted sexual device, breaking the conceptions of the desire and identity as something previously predetermined by purely biological aspects. These conceptions will be fundamental to understand how the approach of homoeroticism varies between different times when portraying subjects that prove very diverse among themselves. We also use the concept of “The place in-between of Latin-American discourse” presented by Silviano Santiago (2013) in order to think how the identity of characters is marked by the exile experience and by exchanges among different cultures. In this complex connection, we verify the possibility of writing homoeroticism and the desire for freedom by subjects within a society that underwent through profound transformations throughout its modernization process.